1993
DOI: 10.1093/bja/71.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Latency Auditory Evoked Potentials During Ketamine Anaesthesia in Humans

Abstract: We studied mid-latency auditory evoked potentials (MLAEP) during induction of general anaesthesia with ketamine 2 mg kg-1. MLAEP were recorded before, during and after induction of general anaesthesia on the vertex (positive) and mastoid (negative) positions. Latencies of the peak V, Na, Pa, Nb, P1 and amplitudes Na/Pa, Pa/Nb and Nb/P1 were measured. Fast-Fourier transformation was used to calculate power spectra of the MLAEP. In the awake state, MLAEP had large peak-to-peak amplitudes and a periodic waveform.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 18 publications
4
40
0
2
Order By: Relevance
“…Evoked potential slope is not typically measured in clinical studies; however, an increase in population event amplitude is usually accompanied by an increase in event slope. Clinical studies have shown mixed results for ketamine, with either maintenance [5] or enhancement [20] of N20-P23 amplitude. The effects of etomidate and ketamine contrast with the volatile anesthetics, tending to reduce the amplitude and increase the latency of cortical evoked responses [3,21] .…”
Section: Results From In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Evoked potential slope is not typically measured in clinical studies; however, an increase in population event amplitude is usually accompanied by an increase in event slope. Clinical studies have shown mixed results for ketamine, with either maintenance [5] or enhancement [20] of N20-P23 amplitude. The effects of etomidate and ketamine contrast with the volatile anesthetics, tending to reduce the amplitude and increase the latency of cortical evoked responses [3,21] .…”
Section: Results From In Vivo Studiesmentioning
confidence: 99%
“…However, there are exceptions that call into question the thalamic gate explanation as a unifying mechanism. Most notable is ketamine, which not only preserves sensory transmission to the cortex [5] , but may even enhance cortical responsiveness to incoming sensory information [6] and maintains an activated EEG.…”
Section: Introductionmentioning
confidence: 99%
“…We did not find significant ketamine effects on the low range of gamma . One study reported that general anesthetic dose (2 mg/kg) ketamine did not change 30-40 Hz power in response to auditory click in humans (Schwender et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps one piece of evidence for the latter position is that the anesthetic ketamine affects MLRs and ASSRs differently. Ketamine anesthesia does not have any significant effects on AMLRs (Schwender, Klasing, Madler, Poppel, & Peter, 1993b), but it increases the amplitude of the ASSR (Plourde, Baribeau, & Bonhomme, 1997). The latter authors note this apparent discrepancy and resolve it by using the actual data presented by the former authors to compute a predicted effect of ketamine on the ASSR, assuming that the ASSR is purely a summation of overlapping AMLRs.…”
Section: Auditory Steady State Responsesmentioning
confidence: 99%